1996
DOI: 10.1159/000129456
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Cholelithiasis after Laparoscopic Cholecystectomy-Behavior of ‘Lost’ Concrements and Their Role in Abscess Formation

Abstract: In two experimental studies we sought preliminary information about the behavior of concrements lost in the peritoneal cavity during laparoscopic cholecystectomy. Materials and Methods: In study 1, human gallstones were analyzed using X-ray diffraction, calssified in three groups and examined with an ultramicroscope; then they were implanted in the peritoneal cavity of rats. After 8 weeks or 6 months, the animals were sacrificed and the concrements analyzed again as before. The tissues surrouding the calculi w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…As shown in several studies, [2][3][4][5][6][7] whether the bile is infected or not, bile and gallstones are at an increased risk for abscess formation and formation of adhesions. The type of stones is one of the factors involved in complication occurrence; more experimental studies and reported cases show that the bacterial contamination is less in cholesterol calculi than in pigment stones (Black, brown or mixed).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in several studies, [2][3][4][5][6][7] whether the bile is infected or not, bile and gallstones are at an increased risk for abscess formation and formation of adhesions. The type of stones is one of the factors involved in complication occurrence; more experimental studies and reported cases show that the bacterial contamination is less in cholesterol calculi than in pigment stones (Black, brown or mixed).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] During laparoscopy, the incidence of gallbladder perforation is 13 to 40%, 21 with a mean of 18. 3%out of those 8 studies with more than 500 LCs.…”
Section: Management Of Gallbladder Perforationmentioning
confidence: 99%
“…In these studies gallstones implanted into the peritoneal cavity not only caused adhesions but also resulted in abscess formation [3,4,9].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these reports describe trocar site abscesses with late discharge of stones or formation of intraperitoneal adhesions. Experimental animal studies have shown that gallstones left in peritoneal cavity, especially when combined with bile, are associated with the formation of adhesions and possible abscess formation [3,4,10,11]. Other experimental and clinical studies that investigated the long-term effect of spilled gallstones did not reveal increased morbidity [2,11].…”
mentioning
confidence: 99%
“…intraperitoneal abscesses, intraperitoneal granuloma, wound infection, etc. Experimental studies have also confirmed that implantation of human gallstones in the peritoneal cavity of rat, rabbit and dog produces intraperitoneal abscesses, sinuses and adhesions, 10,11,12 which states that gallstone is a dynamic viable home of bacteria rather than a tomb.…”
mentioning
confidence: 83%